Gamification in language learning: students' opinion on jenglish / Siti Aishah Taib ...[et al] - Taib, Siti Aishah; Sa’adan, Nadzrah; Mat Saberi, Nurul Izzati; Mat Suri, Nurul Aini; Kasbullah, Nurfarah ‘Aqilah; Murtadza, Fatin Akmal Nabilah; Norhisham, Nur Syahira (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Gamification in language learning is not a new concept and has been studied extensively in the field of education. A language game, Jenglish, was developed by 5 ESL students and supervised by a lecturer. The game was adapted from the famous Jenga game by Leslie Scott. Therefore, this paper aims to present the findings from a case study whereby a group of 22 ESL students played Jenglish in 4 ESL lessons. A set of questionnaire was distributed to the respondents of the study after the last lesson to answer 3 research questions: to investigate ESL students’ opinion on the usefulness of Jenglish on ESL learning, to investigate ESL students’ opinion on the usefulness of Jenglish in relation to affective domain, and to investigate ESL students’ opinion on how Jenglish can be improved. IBM SPSS Statistics 25 and thematic analysis were utilised to analyse the data. The findings revealed positive responses for the first and second research questions while some improvement was suggested in the game’s appearance, content, and rules. Four themes emerged from an open-ended question about the respondents’ opinions of the game which were Compliments, Suggestions to Improve the Game, Benefits, and Others. Whilst findings showed that the game needed improvement, it can be concluded that the respondents found Jenglish useful as a language game.